2021
DOI: 10.1002/jmri.27807
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Exploration of the Application of Vesical Imaging‐Reporting and Data System (VI‐RADS) in Post‐treatment Patients With Bladder Cancer: A Prospective Single‐Center Study

Abstract: Background Vesical Imaging‐Reporting and Data System (VI‐RADS) has been shown to be effective in diagnosing muscle invasion of bladder cancer (BC) in primary patients. Purpose To evaluate the diagnostic efficacy of VI‐RADS in a BC target population which included post‐treatment patients, and to determine the repeatability. Study Type Prospective. Population Seventy‐three patients (42 with primary BC, 31 with post‐treatment BC). Field Strength/Sequence 3.0 T MRI with propeller fast spin‐echo T2WI, echo planer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
7
6
0
Order By: Relevance
“…The area under the curves (AUCs) for the whole study population, primary, and post-treatment groups were 0.945, 0.936, and 0.947, respectively, with noninferiority in the post-treatment group compared to the primary group. 7 The performance of VI-RADS criteria in post-therapy setting agreed with prior reports (AUC range, 0.873-0.960). 8,9 Excellent inter-reader agreement (kappa range, 0.709-0.923) also agreed with previous reports in treatment-naïve populations (kappa range, 0.731-0.92).…”
supporting
confidence: 85%
See 4 more Smart Citations
“…The area under the curves (AUCs) for the whole study population, primary, and post-treatment groups were 0.945, 0.936, and 0.947, respectively, with noninferiority in the post-treatment group compared to the primary group. 7 The performance of VI-RADS criteria in post-therapy setting agreed with prior reports (AUC range, 0.873-0.960). 8,9 Excellent inter-reader agreement (kappa range, 0.709-0.923) also agreed with previous reports in treatment-naïve populations (kappa range, 0.731-0.92).…”
supporting
confidence: 85%
“…The authors found outstanding performance of the VI‐RADS criteria for the diagnosis of MIBC in both clinical settings. The area under the curves (AUCs) for the whole study population, primary, and post‐treatment groups were 0.945, 0.936, and 0.947, respectively, with noninferiority in the post‐treatment group compared to the primary group 7 . The performance of VI‐RADS criteria in post‐therapy setting agreed with prior reports (AUC range, 0.873–0.960) 8,9 .…”
supporting
confidence: 83%
See 3 more Smart Citations